2013
DOI: 10.1007/s40279-013-0101-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigative Trends in Understanding Penalty-Kick Performance in Association Football: An Ecological Dynamics Perspective

Abstract: There have been different approaches to studying penalty-kick performance in association football and in this paper we synthesize key findings within an ecological dynamics theoretical framework. According to this theoretical perspective, information is the cornerstone for understanding the dynamics of action regulation in penalty-kick performance. Research suggests that investigators need to identify the information sources that are most relevant to penalty-kick performance. An important task is to understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
1
11
0
1
Order By: Relevance
“…These are very complex interactive dynamics indeed, but-importantly-affordancebased control gets them into view. In doing so, affordance-based control also directs empirical efforts towards the actual dueling in the penalty box, that is, the evolving interactions between goalkeeper and penalty taker (see Lopes, Araújo, & Davids, 2014b;Lopes et al, 2014a).…”
Section: Future Challengesmentioning
confidence: 99%
“…These are very complex interactive dynamics indeed, but-importantly-affordancebased control gets them into view. In doing so, affordance-based control also directs empirical efforts towards the actual dueling in the penalty box, that is, the evolving interactions between goalkeeper and penalty taker (see Lopes, Araújo, & Davids, 2014b;Lopes et al, 2014a).…”
Section: Future Challengesmentioning
confidence: 99%
“…These findings suggest that the goalkeepers may use a global perceptual strategy by anchoring on the lower distal extremity and the ball whilst extracting essential information from other body segments using peripheral vision. This approach aligns to the research area of ecological dynamics (Lopes et al, 2014), which explains even if a goalkeeper is looking at a predictive source, the perception of information from the performance environment via peripheral vision does not signify the use of that information for action outcome .…”
Section: Discussionmentioning
confidence: 85%
“…In fact, research has consistently shown that the most important visual cues to correctly anticipate the direction of the ball for goalkeepers are from events immediately prior to the striker's kicking action to the striker's foot-to-ball contact (Button, Dicks, Haines, Barker, & Davids, 2011;Dicks, Uehara, & Lima, 2011;Savelsbergh, Van Der Kamp, Williams, & Ward, 2005). However, studies using eye-tracking devices have reported that fixations on the torso, hips and kicking leg of the striker result in successful anticipation of a penalty kick (Lopes, Araújo, & Davids, 2014;Savelsbergh, Williams, Van Der Kamp, & Ward, 2002) although Franks and Harvey (1997) and Savelsbergh and colleagues (2005) have shown that anticipatory skills of goalkeepers were more successful when fixating on the stance leg (i.e., non-kicking leg) prior to foot-to-ball contact.…”
Section: Introductionmentioning
confidence: 99%
“…Kicking performance is the most studied technical action in soccer ( 1 ), and a growing body of research has been dedicated to studying penalty kick performance ( 2 ). Information regarding the “number of kicks” and “number of kicks on target”, usually provided by notational analysis, are important indicators of success in high level competition ( 3 ), and it illustrates the need to understand and train such motor skills.…”
Section: Introductionmentioning
confidence: 99%